Changes in the mechanical parameters of hair in a group of women in reproductive age - Jelen, Karel; Skřontová, Marie; Šimkova, Lucie; Zeman, Josef; Tlapáková, Eva; Fanta, Ondrej (Neuro endocrinology letters, 2014)
OBJECTIVE: Hair quality and scalp characteristics are considered to be a significant marker of health. This marker is reflected in mechanical properties of hair. To investigate these properties, hair samples have been collected among women of different age and then analyzed. The thickness, Young's modulus of elasticity and ultimate strength limit were the main observed parameters. METHODS: The diameter of each hair has been measured using an optical microscope equipped with a digital camera. The hair was then clipped into the uniaxial tensile testing device. Each sample has been stretched to failure at a speed of 2 mm/min and force vs. elongation was recorded. The mechanical results were converted with respect to the diameter and Stress-Strain curve was obtained for each sample. In addition, all the analyzed samples were divided into two groups in dependence on the age, namely samples from women younger than 35 and over 35 years of age. All the measured parameters were statistically evaluated. RESULTS: Young's modulus, yield and elongation parameters showed no significant difference among samples. On the other hand there was a significant difference among the samples in ultimate strength values. Findings from group analysis showed that women under 35 years show about 5 times greater variability in hair strength than that of women above that age. CONCLUSION: The results of our study indicate that hair tendency to grow persists up to 30 years of age, then slowly decreases and then achieves a steady state around 60 years of age.
Keywords: Aging; pružnost; Female; Humans; Tensile Strength; Stress, Mechanical; zdravotní stav; Health Status; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Elasticity Imaging Techniques; Hair; Models, Biological; biologické modely; Elasticity; stárnutí; mechanický stres; dospělí; vlasy, chlupy; pevnost v tahu; Adult; elastografie